Manajemen Proyek Pada Departemen Reliability, Availability And Maintenance (RAM) - Nanda Putra, Yofi; Sharipuddin, Sharipuddin (LPPM Universitas Dinamika Bangsa, 2023)
PT. Pertamina Hulu Rokan Jambi is a company engaged in petroleum which has many branches where one of them is the Jambi field. Currently, the department (RAM) realibility, availability, and maintenance is a division engaged in maintenance engineering. In the business process of maintenance and development work there are several problems faced by the RAM division, including the slowness to monitor the daily progress work, which currently project reporting is received in the form of handwriting which will be recapitulated in the form of an Excel file then it is usually given at the end of the month to the manager. The purpose of this research is to analyze problems and design a web-based project management information system. The research method uses a prototype model and a unified model language system model using usecase diagrams, activity diagrams, and class diagrams. The results of this study are in the form of a prototype design of a web-based project management information system that can be implemented later as a solution to existing problems.